2022
DOI: 10.3390/su142315704
|View full text |Cite
|
Sign up to set email alerts
|

How to Simplify Life Cycle Assessment for Industrial Applications—A Comprehensive Review

Abstract: Life cycle assessment (LCA) has established itself as the dominant method for identifying the environmental impact of products or services. However, conducting an LCA is labor and time intensive (especially regarding data collection). This paper, therefore, aims to identify methods and tools that enhance the practicability of LCA, especially with regard to product complexity and variance. To this end, an initial literature review on the LCA of complex products was conducted to identify commonly cited barriers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 93 publications
(156 reference statements)
0
0
0
Order By: Relevance
“…Over the last decade, there has been an exponential increase in the use of LCA software and databases, such that, nowadays their use is state-of-the-art. Applying this system allows for a standardized procedure, direct connection to LCI databases, and depending on the software, different possibilities to visualize the results, which will aid in their interpretation [42]. Figures 5 and 6, show that the most used software is SimaPro, with GaBi, as the second most used.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, there has been an exponential increase in the use of LCA software and databases, such that, nowadays their use is state-of-the-art. Applying this system allows for a standardized procedure, direct connection to LCI databases, and depending on the software, different possibilities to visualize the results, which will aid in their interpretation [42]. Figures 5 and 6, show that the most used software is SimaPro, with GaBi, as the second most used.…”
Section: Discussionmentioning
confidence: 99%
“…This study measured primary and secondary data on energy and environmental impact emissions from using empty palm oil fruit bunches. Analysis of environmental impacts using the life cycle assessment (LCA) method by ISO 14040 standards using software [7][8][9]. In the life cycle assessment method, there are four stages, including:…”
Section: Methodsmentioning
confidence: 99%
“…The automation and aggregation of an LCA in general and the creation of the life cycle inventory (LCI) in particular are two of the five approaches used to simplify LCA for industrial applications and make the results more usable within product development, as identified by Kiemel et al [18]. Both approaches can enhance practicability when dealing with complex products and high variance because they significantly reduce the effort required for data collection and structuring [18].…”
Section: State Of the Artmentioning
confidence: 99%
“…The automation and aggregation of an LCA in general and the creation of the life cycle inventory (LCI) in particular are two of the five approaches used to simplify LCA for industrial applications and make the results more usable within product development, as identified by Kiemel et al [18]. Both approaches can enhance practicability when dealing with complex products and high variance because they significantly reduce the effort required for data collection and structuring [18]. Advancements in common computer hard-and software, as well as the availability of data resulting from increased digitalisation, enable LCA practitioners to extract and use this data to model, calculate, and assess millions of product configurations in an automated or partly automated fashion [19][20][21][22].…”
Section: State Of the Artmentioning
confidence: 99%